The focal adhesion protein β-parvin controls cardiomyocyte shape and sarcomere assembly in response to mechanical load - Thievessen, Ingo; Suhr, Frank; Vergarajauregui, Silvia; Böttcher, Ralph T.; Brixius, Klara; Rosenberger, Georg; Fleischmann, Bernd K.; Ghanem, Alexander; Krüger, Marcus; Engel, Felix; Fabry, Ben; Bloch, Wilhelm; et al. (Current Biology, 2022)
Physiological and pathological cardiac stress induced by exercise and hypertension, respectively, increase the hemodynamic load for the heart and trigger specific hypertrophic signals in cardiomyocytes leading to adaptive or maladaptive cardiac hypertrophy responses involving a mechanosensitive remodeling of the contractile cytoskeleton. Integrins sense load and have been implicated in cardiac hypertrophy, but how they discriminate between the two types of cardiac stress and translate mechanical loads into specific cytoskeletal signaling pathways is not clear. Here, we report that the focal adhesion protein β-parvin is highly expressed in cardiomyocytes and facilitates the formation of cell protrusions, the serial assembly of newly synthesized sarcomeres, and the hypertrophic growth of neonatal rat ventricular cardiomyocytes (NRVCs) in vitro. In addition, physiological mechanical loading of NRVCs by either the application of cyclic, uni-axial stretch, or culture on physiologically stiff substrates promotes NRVC elongation in a β-parvin-dependent manner, which is achieved by binding of β-parvin to α/β-PIX, which in turn activates Rac1. Importantly, loss-of-function studies in mice also revealed that β-parvin is essential for the exercise-induced cardiac hypertrophy response in vivo. Our results identify β-parvin as a novel mechano-responsive signaling hub in hypertrophic cardiomyocytes that drives cell elongation in response to physiological mechanical loads.
CRIS-Team Scopus Importer:2022-08-05
Keywords: affixin; cardiac hypertrophy; integrin-linked kinase; mechanotransduction; Rac1; sarcomere assembly; β-parvin